THE ROLE OF EARLY CHILDHOOD EDUCATORS IN SHAPE THE CHARACTER OF PANCASILA - Alifah Fauziyah; Hidayati Salamah (Social Sciences and Humanity Studies, 2022)
Pancasila and moral value are very important to be taught from an early age. Attitudes and behavior based on pancasila and moral values can be developed in children, so that children can grow up with noble character in accordance with the expectation of the nation. The purpose of this study was to analyze the importance of teaching pancasila and moral value in early childhood.